La doctrina política de León XIII, principios y actitudes: de Diuturnum illud a Sapientiae christianae (1881-1890) - Coll, Miquel (Archivo Dominicano, 2025)
This article explains the main lines of Leo XIII's political teaching, as expressed in four of his encyclicals on the  subject: Diuturnum illud (1878), Immortale Dei (1885), Libertas (1888), and Sapientiae christianae (1890). The highly complex topic would require a treatment that exceeds the scope of an article such as this. Nevertheless, we wish to show the prudence with which Pope Pecci planned to rebuild the Church's relations with liberal states. At the heart of his teachings was the safeguarding of the Christian conception of man, now subverted by positivism and scientism. He wished to demonstrate that the Church was willing to cooperate with governments for the cause of the common good. But where his teachings culminate is the exhortation to Catholics to get involved in politics, in order to avoid the decisive affairs of society being left in the hands of people who are disaffected or contrary to the faith.